Review. Rivera León, Mauro Arturo, Supermajorities in Constitutional Courts, New York, Routledge, 2024. - Osorio Alvis, María Alejandra (Revista Internacional & Comparada de Derechos Humanos, 2026)
The book Supermajorities in Constitutional Courts by Mauro Arturo Rivera León addresses a highly relevant topic within constitutional law: the impact of supermajority rules on constitutional review of laws in constitutional courts. The central analysis focuses on how supermajorities, understood as requirements of a voting threshold higher than a simple majority to make judicial decisions, are implemented in various jurisdictions to invalidate legislation, highlighting both their benefits and their potential disadvantages in judicial practice.The main objective that guides the different chapters of the book is to examine, through a comparative approach, the different models of supermajorities in various jurisdictions. This includes the reasons that motivate their implementation, the way in which supermajorities were introduced, the motives that led legislators to support such rules, their legal source, the degree of consensus, the evaluation of their effectiveness, and their repercussions for both democracy and the theory of judicial review.